2019
DOI: 10.1039/c9cc04145a
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Mycobacterium tuberculosis transpeptidase LdtMt2 with cysteine-reactive inhibitors including ebselen

Abstract: Inhibitors targeting the conserved nucleophilic cysteine of the mycobacterial l,d-transpeptidases are a potential strategy for the treatment of tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 28 publications
0
49
0
Order By: Relevance
“…These conditions, which provided Z′ and S/B values of 0.82 and 8.1, respectively, are likely to be suitable for high‐throughput screening (HTS). However, to permit HTS, methods for quenching the reaction were sought, and a panel of cysteine reactants was assessed for their ability to react with Ldt Mt2 (unpublished data) . Ebselen, a known cysteine‐reactive reagent, was found to rapidly quench the reaction between Ldt Mt2 and 3 (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…These conditions, which provided Z′ and S/B values of 0.82 and 8.1, respectively, are likely to be suitable for high‐throughput screening (HTS). However, to permit HTS, methods for quenching the reaction were sought, and a panel of cysteine reactants was assessed for their ability to react with Ldt Mt2 (unpublished data) . Ebselen, a known cysteine‐reactive reagent, was found to rapidly quench the reaction between Ldt Mt2 and 3 (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…By targeting cysteine residues in the active site from critical enzymes of Mycobacterium tuberculosis (antigen 85 complex; transpeptidase Ldt Mt2), ebselen and some derivatives were considered promising for treating tuberculosis (de Munnik et al 2019 ; Favrot et al 2013 ; Goins et al 2017 ).…”
Section: Pharmacology Of Organoselenium Compoundsmentioning
confidence: 99%
“… 12 Among the six compounds, ebselen is a clinical candidate with anti-inflammatory and anti-oxidant activities. In preclinical studies, ebselen was reported to react with cysteine residues from completely unrelated proteins including the C-terminal domain of the HIV-1 capsid, 15 the mycobacterium tuberculosis transpeptidase LdtMt2, 16 glutamate dehydrogenase, 17 clostridium difficile toxins TcdA and TcdB, 18 the mycobacterium tuberculosis (Mtb) antigen 85C enzyme, 19 the hepatitis C virus NS3 helicase, 20 and many others. Ebselen was also reported to induce protein unfolding for the insulin-degrading enzyme.…”
Section: Introductionmentioning
confidence: 99%